Study protocol for a cohort study of patients with advanced heart failure in Singapore. Issue 9 (17th September 2018) - Malhotra, Chetna; Foo, Renette; Singh, Ratna; Ozdemir, Semra; Teo, Irene; Sim, David; Jaufeerally, Fazlur; Aung, Than; Keong, Yeo Khung; Nadkarni, Nivedita; Finkelstein, Eric Andrew
Abstract : Introductio: Understanding the symptom and health expenditure burden among patients with advanced congestive heart failure (CHF) and their family caregivers is essential to reform policy and practice needed to provide quality care to these patients at affordable prices. The proposed cohort study titled Singapore Cohort of Patients with Advanced Heart Failure aims to describe trajectories of quality of life among patients and their primary informal caregivers, quantify healthcare utilisation and expenditures, assess changes in patient and caregiver awareness of and preferences for knowing diagnostic and prognostic information, awareness and utilisation of palliative care services, preferences for treatments and decision making, perceived quality of care, self-care, caregiver psychological distress and caregiver burden. Methods: This cohort study will recruit 250 patients with New York Heart Association Classification class III and IV CHF from inpatient wards at two public tertiary healthcare institutions in Singapore. Patients and their primary informal caregiver are being surveyed every 4 months until patients' death; caregivers are followed until 8 weeks postpatient death. Medical and billing records of patients are obtained and merged with patients' survey data. Ethics and dissemination: The study has been approved by an ethics board. Results from the study will be disseminated through publications and presentations targeting researchers, policy makers and clinicians interested in understanding and improving care for patients with advanced CHF. Trial registration number: NCT03089034.